2014
DOI: 10.3151/jact.12.82
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Concrete depending on Cooling Conditions After High Temperature Heating

Abstract: Since the 1960's, various studies have been carried out on the internal and external factors that might affect heated concrete in terms of compressive strength, elastic modulus and thermal stress. In particular, thermal properties of aggregate and cooling methods are known to have a significant influence on concrete residual mechanical properties. This study aims to assess concrete mechanical properties based on the types of aggregate and cooling methods used. The used coarse aggregate in concrete was granite,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It has been reported that 500°C is a critical temperature for self‐compacting concrete exposed to fire and the loss of compressive strength is not critical under this temperature . In the previous papers, the possible reason of such increase of the residual compressive strength with the increase of the heating temperature is explained as re‐hydration due to the steam curing in concrete . Since self‐compacting concrete contains more amount of binders, the re‐hydration effect could become significant.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that 500°C is a critical temperature for self‐compacting concrete exposed to fire and the loss of compressive strength is not critical under this temperature . In the previous papers, the possible reason of such increase of the residual compressive strength with the increase of the heating temperature is explained as re‐hydration due to the steam curing in concrete . Since self‐compacting concrete contains more amount of binders, the re‐hydration effect could become significant.…”
Section: Resultsmentioning
confidence: 99%
“…Within our experimental setup, an electric furnace was installed in a 2000 kN class universal testing machine (UTM, SHIMADZU, Kyoto, Japan) using a steel frame. The temperature was adjusted by applying heat to replicate the conditions of the ISO-834 standard fire curve through preliminary experiments and literature results [ 34 , 35 , 36 , 37 ]. Adjustments were implemented by modulating the electric heater temperature based on measurement of the specimen temperature using a thermocouple (Ø1.6 × 3000 mm sheath + 0.65 mm 2 × 1000 mm thermo shield wire, Jooshin, Incheon, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Karakoç [32] evaluated the compressive strength of light aggregate concretes and demonstrate that it is influenced by the cooling methods. Kim et al [33] concluded that the cooling rate affects the dimensional variation of the aggregates and that the mechanical properties are deteriorated by accelerated cooling. Xiang et al [34] realized that, for slow cooling, the heating temperature influences the residual cracking pattern and failure mode during compression testing.…”
Section: Introductionmentioning
confidence: 99%